Comparisons of steroid, acyclovir, lipoprostoglandin E1 and steroid plus acyclovir treatments in facial paralysis: A rat study - Gök, Ü; Alpay, HC; Akpolat, N; Yoldas, T; Kilic, A; Yilmaz, B; Kabakus, N (Elsevier Ireland Ltd, 2005)
Objective: To induce experimental peripheral facial paralysis by inoculation of HSV1 and to compare the effects of steroid, acyclovir, lipoprostoglandin E2 and steroid + acyclovir treatments in terms of clinical recovery, electrophysiologically and histopathologically. Materials and methods: A total of 132 adult female rats were used in this study. HSV type 1 strain was inoculated at the back of the left ear by using 27 gauge needle. Of all animals, 70 (53%) rats which developed facial paralysis were divided into five groups (n = 14 for each group) as control, steroid + acyclovir, lipoprostaglandin El, steroid only and acyclovir only. At the end of the 21 days period, the rats were clinically examined and electrophysiological tests were performed, then decapitated and the nerve specimens were obtained. Results: A modified electroneurography (ENoG) test was performed and the latencies and the amplitudes were compared. The findings of the intact side were better, but with no significant difference. Histopathologicaly edema was significantly smaller in all. groups compared to the controls (p < 0.05). Similarly, no difference was seen in terms of vacuolar degeneration and Schwann cell hyperchromatisation among the groups and no significant difference in recovery period and rate of facial paralysis when all groups were compared. Conclusion: Facial paralysis induced by HSV1 recovered spontaneously within a week. In the treatment of facial paralysis, steroid alone, acyclovir alone, steroid + acyclovir, or lipoprostaglandin E1 all reduced edema in the infected facial nerve but there was no statistical difference in of the rate or degree of recovery. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bell's palsy; steroid; acyclovir; lipoprostoglandin E1; facial paralysis in rat